Images of Interrelationship in the Contemporary Iraqi Architectural Product: صور التعالق في النتاج المعماري العراقي المعاصر - Sarah Majid Al-Khatawi, Parizat Qassim Hussein Fehmi (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
This research aimed to reveal the images of attachment that the Iraqi designer produces in the contemporary Iraqi architectural product in an attempt to address the research problem that centered on (the lack of clarity of the images of interrelationship produced by Iraqi architects in the contemporary Iraqi architectural product). As for the research methodology, it is determined by defining the special framework for research In order to get acquainted with the concept of attachment and its application to elected Iraqi contemporary architectural products, and then discuss and analyze the results of that application, up to the conclusions that have been shown in general there is a desire and orientation of contemporary Iraqi designers to cope with contemporary trends and in particular the post-structural trends that emphasize the creative outcomes that include Several levels of meaning and rich in their connections that transcend the frameworks of familiar and direct, break the limitations of traditional models and open the horizons of interpretation and significance.